PELAKSANAAN AKREDITASI BERBASIS ONLINE DI SEKOLAH DASAR - Sukardi sukardi (UNIVERSITAS BENGKULU, 2019)
This purpose to describe the implementation of elementary school 62 Seluma accreditation. The approach and method of research is using qualitative descriptive study with case study approach. Data collection techniques in this study obtained through interviews, observation, documentation. Subjects were principals, teachers, committees. Data analysis is done by Reduction, presentation, verification. The result of the research shows the collection of documents for the establishment of online accreditation preparation team, data collection and supporting information, online accreditation instrument accreditation, school effort in complementing the eight national standards of education. Conducting visitation by the assessor team is a clarification, verification and validation activity done by comparing the data and information with real condition of the school through field observation, class observation, interview. Accreditation at elementary school sixty two Seluma based online using SisPenA application.Keywords: Online based accreditation, Qualitative descriptive study